ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN WAKTU PELAKSANAAN PROYEK KONSTRUKSI BANGUNAN FASILITAS PARIWISATA (Studi Kasus : Kabupaten Badung dan Gianyar) - Ida Bagus Gede Indramanik; Juniada Pagehgiri; Ade Darma Erlangga (Jurnal Teknik Gradien, 2023)
In the construction of tourism facility projects there are factors that can affect the delay in the implementation time. The impact of these factors is the delay of a project. Project delays arise when the contractor cannot complete the project according to the time stated in the contract. The purpose of this study is to determine the effect of each factor on the delay of a project at a tourism destination in Bali. Data collection was carried out by survey using a questionnaire which was distributed to 31 respondents. Respondents were taken based on the multi random sampling method where the first stage is the tourist area that will be used, the second is the project for each tourist area and finally the parties directly involved in working on a project in the field (proportion). The data analysis used is in the form of multiple linear regression tests to determine the factors that have a significant effect on the delay in the implementation time of tourism facilities in Bali using SPSS (Statistical Package for the Social Sciences) software version 26. From this test, there are 5 factors that have a significant effect on tourism facility development projects in Bali, namely: Labor factor (X1) with an influence value of 3,950, Material factor (X2) with an influence value of 2,410, Equipment factor (X3) with an influence value of 2,582, Financial factor (X4) with an influence value of 2,478 , Factor method (X5) with an effect value of 2,175 , and the influence of all factors simultaneously with a value of 41,225.